New data about a Kimmeridgian larger foraminiferal assemblage from a section cropping out NW of Los Reyes Metzontla, Puebla, Mexico - Lourdes Omaña; Delfino Hernández-Láscares; Blanca Estela Buitrón; Fernando Nuñez-Useche (Revista Mexicana de Ciencias Geológicas)
Northwest of Los Reyes Metzontla, Puebla, a rock succession outcrops that is composed of limestone and sandstone that contain larger foraminifera as well as bivalves such as Trichites sp., corals, and stromatoporid Cladoropsis mirabilis.  From the beds with Trichites, we found an assemblage of larger foraminifera that is composed of the species Pseudospirocyclina mauretanica, Choffatella tingitana, Pseudocyclammina lituus, Everticyclammina virguliana, E. praekelleri, Rectocyclammina chouberti, Mesoendothyra croatica, Nautiloculina oolitica, Siphovalvulina variabilis, and Coscinoconus alpina. In the present work, this association was dated as Kimmeridgian age (Late Jurassic) and represents an important record, since rocks of this age have not previously been reported in this area. The larger benthic foraminifera identified in the studied material inhabited the shallow-water environments which were widely distributed around the Tethys during the Late Jurassic.